Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages 18 schemes, or through loss of annual livelihood ; (2) it may grant supplementary pensions to persons over 60 years of age who are receiving Old Age or Widows' Pensions ; and (3) it may undertake the rehabilitation of the workless. The Board's scales are now as follows :— Unemployment Assistance Supplementary Pensions. If the applicant is a householder : Husband and wife 35/- 36/- 37/- (if both pensioners) Male householder 20/6 22/6 Female householder 19/6 21/6 Children: Under 5 4/9 4/9 Aged 5-7 5/3 5/3 Aged 8-10...................... 5/9 5/9 Aged 11-13 6/3 6/3 Aged 14-15 7/9 7/9 Dependants : 16-20 12/6 12/- 21 and over (male) 14/6 14/- 21 and over (female) 13/6 13/- (Some adjustment of the scale rates is made where rent is high.) Thus a husband and wife and two children aged, say, 4 and 6, would get 45/-. It will be remembered that Sir William Beveridge's minimum income for a family of this size was 48/6 in 1940, since when the cost of living has risen. Until the Determination of Needs Act, 1941, assistance was dependent on a means test, in which the income earned by any member of the distressed person's family who were living at home was taken into account in assessing relief. This was rightly resented. It subjected the applicant to deep humiliation ; it made him a burden on his relatives, and was grossly unfair to them ; and it split up families by inducing young people to leave home in order to avoid the compulsory contribution to their parents' or relatives' upkeep. Since 1941, non-dependent members of the household are merely assumed to make a contribution to household expenses on the following scale, and these amounts are deducted from the relief which would otherwise be given :— From a wage of 35/- contribution 7/- " " 30/- to 55/- " 5/- " " 20/- to 30/- " 2/- " " below 20/- " Nil. The Board's achievements in the retraining of the workless are by no means noteworthy. The following table shows the approximate number of applications who were trained in various types of centre in 1938 :— Centre. Number of Applicants trained. Government training 5,900 Instructional 20,236 Local training by voluntary bodies 2,628 30,915 15X/2/98/13